Rheumatoid factor seropositivity is inversely associated with oral contraceptive use in women without rheumatoid arthritis. Issue 2 (25th July 2006) - Bhatia, Shailaja S; Majka, Darcy S; Kittelson, John M; Parrish, Lezlie A; Ferucci, Elizabeth D; Deane, Kevin D; Arend, William P; Rewers, Marian; Michael Holers, V; Norris, Jill M
Abstract : Objectives: To examine whether oral contraceptive use is associated with the presence of serum rheumatoid factor in women of reproductive age without rheumatoid arthritis. Methods: 304 women selected from parents of children who were at increased risk of developing type 1 diabetes were studied, because they were enriched with the human leucocyte antigen-DR4 allele, a susceptibility marker for both type 1 diabetes and rheumatoid arthritis. Participants visited a clinic where blood was drawn for rheumatoid factor testing, and exposure data were collected via questionnaires. A medical history and joint examination were performed to rule out rheumatoid arthritis. Participants and examiners were unaware of the participants' rheumatoid factor status at the time of examination and questionnaire. Results: Use of oral contraceptives at any time was inversely associated with rheumatoid factor positivity (adjusted odds ratio (OR) 0.2, 95% confidence interval (CI) 0.07 to 0.52) independent of age, education and smoking. Smoking ⩾20 pack-years was also associated with rheumatoid factor positivity (adjusted OR 56.38, 95% CI 4.31 to 736.98) compared with never smoking. Smoking 1–19 pack-years was not associated with a positive rheumatoid factor. Conclusions: Our results suggest that oral contraceptive use, and possibly cigarette smoking, act early in the development of the immune dysregulation that occurs in rheumatoid arthritis.